PENGARUH PELATIHAN BERBASIS RISIKO PADA PENINGKATAN KOMPETENSI APARATUR SIPIL NEGARA - Syafitri, Netti; Permata Sari, Dewi; Sumardin, Sumardin; Maizar, Maizar; Sabri, Sabri (CV. Lafadz Jaya, 2024)
The research entitled